INTRODUCTION OF DIFFERENT SPECIFICATIONS OF NAVIGATION POSITIONING ACCURACY BASED ON THE PBN PERFORMANCES BY THE DME/DME - Bogunenko, Mykola; Mishchenko, Victor (Proceedings of National Aviation University (archive), 2014)
The article describes the strategy implementation of performance based navigation in Ukraine. The authors investigated the accuracy of the aircraft position using DME/ DME as a navigation aid and the possibility of simplifying the construction zone correction for a given accuracy. The simulation results on prescribed accuracy zones defining with the aid of program developed by the authors of the article are provided.